Flexible Conductive Composites for Electronic Skin Applications: A Review - Han, Xiaotian (Exploring Science Academic Conference Series, 2026)
Research into electronic skin, or e-skin, has evolved into a fast-moving field. Researchers aim to build artificial systems with sensing performance matching human skin. Robotics, wearable electronics, and healthcare monitoring tools are all seeing rapid p rogress. This has generated strong demand for flexible sensors that fit curved surfaces and detect signals such as pressure, strain, and temperature. Many material systems are currently being tested for e-skin devices, among which flexible conductive composites deliver clear advantages. These materials combine conductive properties, stretchability, and sound mechanical resilience, making them highly practical for e -skin construction. This review surveys the latest progress in conductive composite materials for e-skin across five dimensions —material systems, conduction mechanisms, sensing principles, structural design strategies, and practical deployment hurdles. It examines representative conductive fillers (carbon nanotubes, graphene, MXene, silver nanowires, and conductive hydrogels) alongside their polymer hosts, compares charge -transport behaviors and sensing modalities across different composite families, and analyzes how micro - and nano -scale structural engineering boosts sensitivity, f lexibility, and durability. Mainstream fabrication routes, real -world application scenarios, and persistent technical obstacles are also discussed, along with emerging directions such as self-healing materials and self-powered e-skin architectures. By trac ing the links among material choice, sensing mechanism, device architecture, and application requirements, this paper clarifies what existing conductive composite systems can and cannot deliver, and offers a forward-looking perspective on where intelligent e-skin sensing systems may head next.